Ecosystem health assessment of Sungai Pengkalan Chepa Basin: water quality and heavy metal analysis - Mohd Saifuddin Maliki Abdullah,; Maliki Hapani,; Nur Fatien Muhamad Salleh,; Wan Mohd Sahnusi Wan Alias, (Penerbit Universiti Kebangsaan Malaysia, 2020)
This study was to determine the ecosystem health status at Sungai Pengkalan Chepa Basin based on Water Quality Index (WQI) and heavy metal concentration in the river water. Water samples were collected from 11 stations along the river and they were analyzed using YSI 556 MPS and laboratory analysis for in-situ test and ex-situ test, respectively. Meanwhile, heavy metal concentrations were analyzed using AAS. Water sampling was carried out starting from November 2018 until June 2019. The results for total median value of water quality parameters were as follows; DO (2.72 mg/L), BOD (6.42 mg/L), COD (33.5 mg/L), AN (1.02 mg/L), TSS (27 mg/L), and pH (6.97). According to WQI, Sungai Pengkalan Chepa Basin is classified under Class III, therefore, it is considered as slightly polluted. The order of concentration of heavy metals in water is Fe > Cr > Zn > Cu > Cd. Most of the heavy metals were found within the permitted level of National Drinking Water Quality Standard (NDWQS) except for Cd. Based on the Kruskal Walis test, there was a significant difference between parameters namely DO, BOD, COD, AN, pH, Zn, and Cd with sampling locations (ρ < 0.05). Based on this study, it can be concluded that the ecosystem health of Sungai Pengkalan Chepa Basin is not healthy from the aspects of DO, BOD, COD, AN, and Cd. The water quality status of Sungai Pengkalan Chepa Basin was mainly affected by the anthropogenic activities from urban development.